IPR 99 - Dwarf arabica coffee cultivar resistant to coffee ringspot virus - Sera,Tumoru (2013)
'IPR 99' was derived from a cross between "Villa Sarchi 971/10" and "Hibrido de Timor 832/2". It is a dwarf cultivar, resistant to coffee ringspot virus, partially resistant to leaf rust with semi-late ripening. 'IPR 99' presents partial resistance to necrosis and mummification of young fruits on field conditions. It presents special cup quality and high yield in lower and higher temperature coffee regions in Paraná State.